Ocular pathology in patients referred to ophthalmology outpatient clinic at tertiary care hospital with headache (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Headache has multi-factorial causes; many primary or secondary headache disorders have ocular manifestations and benefit from the systematic ocular examination. Physicians at the point of the first contact should therefore be familiar with common ocular pathologies associated with a headache for appropriate referral.Method: This hospital-based descriptive cross-sectional study was conducted in the Ophthalmology Department of Patan Hospital. All patients with headache as primary symptom and were referred to an ophthalmology clinic for ocular evaluation by other departments were included. The study was done for 15 mo and 354 patients were evaluated for the cause of headache. Findings and diagnoses of consenting participants were recorded and analyzed.Result: All enrolled patients completed all the study procedures and were analyzed. The majority 61% were in 14-40 years. Homemaker was commonly affected 30.2% followed by students 25.4%. Any form of ocular pathology was detected in 76 % of patients. The majority of patients had no refractive errors (67.8%). Although any form of refractive error was more common in the presbyopia age group there was no statistically significant difference between different age groups. Most patients were orthophoric and only 11% of patients had vergence insufficiency. Among the ocular pathology dry eye, glaucoma suspects were more common.Conclusion: This study supports the ocular morbidities and headache symptoms are linked very frequently. Good ocular history is needed for appropriate patient referral to a specialist. Correction of a minor degree of refractive error and lubricating eye drop may relieve worrisome headaches for many patients.